_ From Hegel to Adorno, The philosophical understandig of art - Gutierrez Pozo, Antonio (Fedro, Revista de Estética y Teoría de las Artes, 2020)
In this piece of work we seek to present Adorno’s aesthetic theory like an appropriate proposal to specify the nature and the current philosophical status of aesthetics, beyond the aesthetic approaches of Hegel and of -recognizing the impropriety of the use of the term ‘aesthetics’- Heidegger, although in fact recognizing that Adorno’s aesthetic conception is precisely beginning to take definite shape in the debate with them, especially with the Hegelian position. Nevertheless, Adorno’s aesthetic theory joins in principle with the fundamental thesis of Hegel and of Heidegger in the sense of affirming the philosophical/epistemological and ontological relevance of art, opposite to the other perspective that has largely configured the modern understanding of the aesthetics, the one that starting from Kant and that passing to Kierkegaard, culminates in the Positivism. The compartmentalization of Kant about knowledge finally granted the rights of the knowledge and the truth to the science exclusively, affirming that the aesthetic judgement -the art – does not contribute any knowledge about their objects1 .